Augmenting rice ANNEXIN expression to counter planthopper Nl Annexin-like5 as an antivirulence strategy against a major crop pest - Xiao-Ya Zhang; Shaoqin Li; Comzit Opachaloemphan; Chuan-Xi Zhang; Sheng Yang He; Yanjuan Jiang (Proceedings of the National Academy of Sciences, 2025)
The brown planthopper (BPH) is the most devastating insect pest in rice, posing a serious threat to global rice production. One attractive control strategy would be based on the understanding of the virulence mechanisms of BPH at the molecular level and then designing targeted methods to neutralize such mechanisms. Salivary proteins of BPH are important players in mediating rice–BPH interactions. Here, we describe a pivotal role of a watery saliva protein, Nilaparvata lugens Annexin-like5 ( Nl ANX5), in the rice–BPH interaction. RNA interference (RNAi) of NlANX5 greatly compromised BPH feeding performance and survival rate on rice plants. NlANX5 -RNAi BPH triggered a rapid calcium ion influx in rice cells. The feeding and survival defects of NlANX5 -RNAi BPH can be restored in NlANX5 -expressing transgenic rice plants. Nl ANX5 targets rice annexin ( Os ANN) proteins, including Os ANN2 and Os ANN8. Further analysis with Nl ANX5 and Os ANN2 as well as Os ANN8 showed that Nl ANX5 displaces Os ANN2 and Os ANN8 from the rice cell membrane. The osann2 osann8 mutant rice plants are hypersusceptible to BPH infestation. In contrast, enhanced expression of OsANN2 and OsANN8 genes resulted in robust rice resistance against BPH. This study highlights a successful example of identifying and augmenting the expression of the host targets of a major BPH virulence effector as a promising antivirulence strategy against an important crop pest.